Rapid isolation of pan-neutralizing antibodies against Omicron variants from convalescent individuals infected with SARS-CoV-2 - Yu, Peng; Ran, Jingping; Yang, Ruiqi; Zhu, Hang; Lu, Song; Wu, Yuzhang; Zhao, Tingting; Xiong, Tianchen (Frontiers in Immunology, 2024)
Introduction The emergence of SARS-CoV-2 Omicron subvariants has presented a significant challenge to global health, as these variants show resistance to most antibodies developed early in the pandemic. Therapeutic antibodies with potent efficacy to the Omicron variants are urgently demanded. Methods Utilizing the rapid antibody discovery platform, Berkeley Lights Beacon, we isolated two monoclonal neutralizing antibodies, 2173-A6 and 3462-A4. These antibodies were isolated from individuals who recently recovered from Omicron infections. Results Both antibodies, 2173-A6 and 3462-A4, demonstrated high affinity for the RBD and effectively neutralized pseudoviruses from various Omicron lineages, including BA.4/5, XBB.1.16, XBB.1.5, and EG.5.1. This neutralization was achieved through binding to identical or overlapping epitopes. Discussion The use of the Beacon platform enabled the rapid isolation and identification of effective neutralizing antibodies within less than 10 days. This process significantly accelerates the development of novel therapeutic antibodies, potentially reducing the time required to respond to unknown infectious diseases in the future.